Development of Explanation Text Teaching Materials Based on Needs Analysis of Learning for Junior High School of Class VIII SMP Negeri 28 Medan - Indah Oktasya Sihombing; Malan Lubis; Mutsyuhito Solin; Martua Reynhat Sitanggang Gusar (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
Research and development aims to produce products in the form of explanatory text teaching materials as well as to test the effectiveness of the products that can be used by grade VIII students of SMP Negeri 28 Medan as one of the ways to improve the quality of learning. The results of the validation from material experts in the development of explanatory text teaching materials for students showed that the feasibility of the teaching material components with an average of 88.54 on very good criteria and the feasibility of material substance with an average of 90.91 on very good criteria. Thus, the explanatory text teaching materials developed as a whole are included in the "very good" criteria. The results of module validation by learning design experts concluded that the learning design developed was in the "very good" criteria with a total average percentage of 91.00%. Thus, the feasibility of the design of the explanatory text teaching materials developed can be used by students. The results of the responses made by the Indonesian language teacher concluded that the explanatory text module was included in the "very good" criteria with a total average percentage of 99.26%. So it can be stated that there are differences in learning outcomes between students who use explanatory text teaching materials and those who use textbooks and it can be concluded that the teaching materials developed are effective and suitable for use as learning resources.